1997
DOI: 10.1109/16.641353
|View full text |Cite
|
Sign up to set email alerts
|

A silicon micromachined scanning thermal profiler with integrated elements for sensing and actuation

Abstract: The thermal profiler is a scanning probe microscope with a miniature thermocouple (TC) at its tip which provides topographic and thermographic information by sensing heat conducted across a small air gap. The silicon micromachined thermal profilers (SMTP's) described in this paper are structurally comprised of a probe that can be longitudinally actuated by an integrated electrostatically driven suspension. A polysilicongold TC is located near the probe tip, which overhangs a glass substrate; a resistive heater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2025
2025

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…The resistive heater located at the base of each probe permits in-situ testing of the TCs [10]. The TC output is monitored while the junction near the probe tip is held at room temperature and the junction at the base is heated by the resistor.…”
Section: Measurement Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resistive heater located at the base of each probe permits in-situ testing of the TCs [10]. The TC output is monitored while the junction near the probe tip is held at room temperature and the junction at the base is heated by the resistor.…”
Section: Measurement Resultsmentioning
confidence: 99%
“…Its lower limit, which is relevant only in contact mode, is constrained by the effective contact and spreading (thermal) resistance at the probe tip. In noncontact mode, it can be shown that for a given R , the temperature drop along the probe length is highest when R R [10]. Since R generally exceeds 10 kW and varies with operating conditions, the design guideline is to maximize R .…”
Section: Structure and Operationmentioning
confidence: 99%
“…Electrical resistance thermometry was introduced in [21], using a Wollaston wire shaped like a cantilever, enabling simultaneous thermal and AFM imaging. A surface micromachined thermal probe with integrated 1D electrostatic actuation was reported in 1997 [22]. A CMOS thermal probe with integrated piezoresistive detection is described in [23].…”
Section: Scanning Probe Microscopymentioning
confidence: 99%
“…Such a problem is frequently encountered in MEMS/NEMS devices as in, for example, the scanning thermal profiler [29][30][31]. Figure 4 illustrates the simulation model.…”
Section: B Fourier Thermal Problemmentioning
confidence: 99%